(untitled) (London Journal of Research In Science: Natural and Formal, 2025)
This paper proves that Goldbach’s conjecture is true. The proof uses Gaussian modular arithmetic to calculate thenumber of pairs of odd numbers, KT , whose sum is a given even number, n, as well as, the number, KE, of those that can potentiallycontain prime numbers.Next, a probabilistic model with a binomial probability distribution is de ned, which will be applied to KE to calculate a functionf(x) for the expected value, E(X), where X is the number of pairsformed by two prime numbers.Finally, the analysis of this function, f(x), will allow us to provethat the conjecture is true.